(untitled) (Archaeologia Adriatica, 2009)
In the northern Dalmatia region where there were only two cultural systems throughout the Bronze and Iron Ages, four moments are crucial in the use of cremation ritual during the 2nd/1st centuries BC: in the Early Bronze Age (Cetina culture: Ervenik, Podvršje − Matakov brig, Nadin, Krneza − Duševića glavica), in the Early Iron Age (Nadin, mound 13, Krneza − Jokina glavica), in Hellenism (Dragišić, gr. 4 A-C), and finally, for the first time very intensively during the Romanization of Liburnians. Newly discovered cremations in ceramic urns (gr. 3, 13) in burial mound 13 (9th – 6th cent. BC) from Nadin near Benkovac are the first example (after Dragišić) of Liburnian cremation; more precisely, burial mound 13 with 19 graves represents a form of biritualism in the Liburnians. It is also an example of the greatest number of Liburnian burials under a mound, with crouched, extended and cremated skeletons and many ritual remains (traces of fire on the ground and on animal bones: funerary feast?; numerous remains of ceramic vessels (libation?). Although typical Liburnian burial "inherits" many formal and symbolic elements (stone cist, enclosing wall, libation, etc.) from the (Early) Bronze Age (and probably Eneolithic as well), cremation in the Liburnian burial mound 13 from Nadin cannot be explained in terms of continuity from the Early Bronze Age; links are missing, particularly those from the Middle Bronze Age in the study of the cultural dynamics of the 2nd millennium BC in the northern Dalmatia region. Squat form of the Nadin urns with a distinct neck has analogies in the Liburnian (Nin) and Daunian funerary pots for burying newborns (ad encytrismos), and also in the typology of pottery (undecorated or decorated) in a wider region (Ruše, V.Gorica, Dalj/Vukovar, Terni II, Este, Bologna I-II, Roma II, Cumae I, Pontecagnano IA, Histrians, etc.), i.e. in the forms widespread from the Danubian region, Alps, and Balkans to the Apennine Peninsula between the Late Bronze and Early Iron Ages (10th/9th – 8th cent. BC). Although appearance of cremation in the Picenian culture has not been completely clear (Fermo necropolis, burials from Ancona, Numana, Novilara: graves Servici, 29, 39 from Piceno II-III, from the 8th/7th.cent. BC), Liburnian culture is most similar to the Picenian culture in the Adriatic world by the intensity and period of cremation, and form of urns. Specifically, decorated urn in a male grave 52 from Numana from the 9th century BC is analogous to the Nadin urns. This grave from Numana is usually mentioned as an example of trans-Adriatic, Picenian-Liburnian (Balkanic) i.e. Picenian-Histrian relations. Liburnian urns are similar to the urn from the grave in Numana, 495, Davanzali, from the late 9th century by their profilation. "Genesis" of both Liburnian and Picenian cremation is unknown. They are two convergent phenomena, reflecting the "unity" of the late Urnenfelder world of the 10th/9th centuries BC and resulting from cultural-ethnical contacts in a "closed circle" from the Danubian region – southeastern Alpine region – Apennine Peninsula, supported by smaller migrations in the first centuries of the Iron Age, from the trans-Adriatic direction in Picenum (with definite Villanova influence), and in Liburnia probably from the hinterland. In this Adriatic circle in the first centuries of the Iron Age multiple cultural contacts between Liburnians, Histrians and Picenians are for now a good (initial) context for a more detailed interpretation of Liburnian cremation. Despite the aforementioned, it is not necessary to relate directly the structure (ritual, goods) of gr. 52, Numana – Qualiotti to Histrian patterns nor the grave 495, Numana-Davanzali to the Iapodian ones. Cremated Liburnian burial from the Early Iron Age represents a certain continuity and a "reflection" of the late Urnenfelder circle, which was manifested in different ways in the beginnings of the Liburnian, Picenian, and Histrian cultures and elsewhere. The latest excavations on a planned Liburnian-Roman necropolis in Nadin (Nedinum) provided us with new information about the spatial, chronological and symbolical relation (religious, social) between the autochtonous Liburnian and Roman component in the period of Romanization of northern Dalmatia.